Increasing learning outcomes of social sciences on natural resources materials using think pair check learning model and image media in student - Nur Salim; Suharsono Suharsono; Roko Patria Jati (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2021)
This study aims to determine whether the use of theLearning Model Think Pair Check and Picture Media can improve social studies learning outcomes for the fourth grade students of MIN Salatiga. This research is a classroom action research consisting of two cycles with 4 stages, namely planning , implementation, observation, and reflection. The subjects of this study were students of Class IV MIN Salatiga, totaling 34 students. The research instruments were in the form of observation sheets, test questions and documentation. Data collection techniques used in the form of observation, interviews, documentation and tests. The data were analyzed statistically and the cycle was stopped when 85% of students had completed the KKM. The results showed that the use of the Think Pair Check learning model and image media could improve social studies learning outcomes for fourth grade students at MIN Salatiga. The increase in students' learning mastery from Pre-Cycle to Cycle I was 26.46% and Cycle I to Cycle II was 20.59%.